Attribution De Recompense Dans l’Enseignement du Français de la Classe XI SMA Angkasa 1 Halim Perdana Kusuma - Andreani, Phobe; Ekowati, Sri Harini; Savitri, Dian (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2021)
Abstract Cette ÃƒÂ©tude a pour objectif de savoir si les enseignants donnent souvent une rÃƒÂ©compense dans l'apprentissage du franÃƒÂ§ais en classe XI SMA Angkasa 1 Halim Perdana Kusuma. L'approche de cette recherche est quantitative descriptive. Dans cette ÃƒÂ©tude, les donnÃƒÂ©es sont obtenues en donnant des questionnaires ÃƒÂ 51 ÃƒÂ©lÃƒÂ¨ves de la classe XI SMA Angkasa 1 Halim Perdana Kusuma par Google Form et accompagne dÃ¢â‚¬â„¢un entretien menÃƒÂ© avec un enseignant sur le sujet de franÃƒÂ§ais au SMA dont le but est de connaÃƒÂ®tre la rÃƒÂ©compense qui se fait en classe. En raison de la pandÃƒÂ©mie covid-19, les activitÃƒÂ©s des entretiens ont ÃƒÂ©tÃƒÂ© menÃƒÂ©es en ligne par l'application de messagerie WhatsApp. BasÃƒÂ© sur les analyses de la recherche le rÃƒÂ©sultat montre que lÃ¢â‚¬â„¢enseignant utilise la rÃƒÂ©compense dans les sujets de franÃƒÂ§ais pour les ÃƒÂ©lÃƒÂ¨ves de la classe XI SMA Angkasa 1 Halim Perdana Kusuma. La rÃƒÂ©compense donnÃƒÂ©e par l'enseignant aux ÃƒÂ©lÃƒÂ¨ves de la classe XI SMA Angkasa 1 Halim Perdana Kusuma est divisÃƒÂ©e en deux types, ce sont la rÃƒÂ©compense verbale donnÃƒÂ©e par des mots de compliments et la rÃƒÂ©compense non verbale donnÃƒÂ©e par la fourniture d'une note supplÃƒÂ©mentaire aux ÃƒÂ©lÃƒÂ¨ves.. Abstract This study has the objective to find out whether the teachers often give a reward in learning French in Class XI SMA Angkasa 1 Halim Perdana Kusuma.The approach of this research is quantitative descriptive with the survey method. In this study, the data obtained by giving questionnaires to 51 students of Class XI SMA Angkasa 1 Halim Perdana Kusuma via Google Form and equipped with an interview conducted with a teacher on French subjects at the SMA whose purpose is to know the reward that is done in class. Due to the covid-19 pandemic, the activities of the interviews were conducted online through the WhatsApp messaging app.Based on the results of the research that has been done, showing that the teacher uses the reward in French subjects for students of Class XI SMA Angkasa 1 Halim Perdana Kusuma. The reward given by the teacher to the students of Class XI SMA Angkasa 1 Halim Perdana Kusuma is divided into two types, namely the verbal reward given by words of compliments and the non-verbal reward is given by providing additional value to the students..